Spatial Approach and Territorial Views of the Regional Development in Ecuador (1952 - 1982). Studies, Projects and Plans - Nufrio, Anna Vincenza (2017)
The change of scale of the political-economic processes imposed by globalization are increasingly orienting, in Europe, Asia and Latin America, the territorial planning practises towards the implementation of regional and sub-regional development strategies. “Regionalization” is a pending issue in Ecuador’s political agenda and, although the current Constitution establishes that the  country is organized territorially in regions, provinces, cantons and rural parishes, equitable development, autonomy and decentralization of the different government levels remain an objective to achieve. This article supports this debate by investigating the spatial approach and the territorial views that guided the regionalization proposals in Ecuador between 1952 and 1982. To this end, valuable documents (studies, plans and projects) carried out by the JUNAPLA and the CREA have been analyzed: unique attempts of Regional Planning carried out in the country, especially in the Center-South Region.